STRATEGI BISNIS TERHADAP KINERJA BISNIS DIMEDIASI KEMAMPUAN MANAJERIAL (Studi pada Industri Kecil Menengah Ecoprint di Kota Kediri) - Hidayati, Nur (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The objectives of the research, among others, are to: (1) determine the effect of business strategy on managerial ability in IKM ecoprint in Kediri City, (2) determine the effect of business strategy on business performance in IKM ecoprint in Kediri City, (3)determine the effect of managerial ability on performance business at IKM ecoprint in Kediri City, (4) knowing the effect of business strategy through managerial ability on business performance at IKM ecoprint in Kediri City. This research was conducted on ecoprint batik SMEs in Kediri City. Data analysis used path analysis with SPSS 21.0 program. 2 The results of hypothesis testing are as follows: business strategy has an effect on managerial ability; managerial ability affects business performance; business strategy affects business performance; and business strategy has an effect on business performance through managerial ability as a mediating variable.